Enantioselective Behavior of Flumequine Enantiomers and Metabolites' Identification in Sediment. (2nd December 2022) - Xue, Moyong; Gu, Xu; Qin, Yuchang; Li, Junguo; Meng, Qingshi; Jia, Ming
Abstract : The enantioselective adsorption, degradation, and transformation of flumequine (FLU) enantiomers in sediment were investigated to elucidate the enantioselective environmental behaviors. The results of adsorption test showed that stereoselective differences of FLU enantiomers in sediment samples and the adsorbing capacity of S -(−)-FLU and R -(+)-FLU are higher than the racemate, and the pH values of the sediment determined the adsorption capacity. Enantioselective degradation behaviors were found under nonsterilized conditions and followed pseudo-first-order kinetic. The R -(+)-FLU was preferentially degraded, and there was significant enantioselectivity of the degradation of FLU. It can be concluded that the microorganism was the main reason for the stereoselective degradation in sediments. The physicochemical property of sediments, such as pH value and organic matter content, can affect the degradation rate of FLU. In addition, the process of transformation of FLU enantiomers in water-sediment system had enantioselective behavior, and R- (+)-FLU was preferential transformed. Meanwhile, the main metabolites of FLU in the sediment were decarboxylate and dihydroxylation products. This study contributes the evidence of comprehensively assessing the fate and risk of chiral FLU antibiotic and enantioselective behavior in the environment.